Orality, narrative, rhetoric: new directions in Mishnah research - Rozen-Tsevi, Yishai (AJS review, 2008)
The appearance in recent years of an impressive series of books, articles, and mainly dissertations on various aspects of the Mishnah collectively signifies something greater than the sum of its parts. These works herald the emergence of a new wave of Mishnah research. While differing significantly in their themes and methods, all the works discussed here share some basic methodological assumptions that are not shared by more “traditional” studies. Among these are a holistic attitude to the Mishnah as a composition; interest in questions of variegation of genre and style (narratives, rituals, lists, etc.); sensitivity to literary devices and techniques; and the use of new interpretive paradigms from rhetoric, cultural, and performative studies.